THE IMPACT OF AI ON STUDENTS' CRITICAL THINKING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the impact of artificial intelligence (AI) on students’ critical thinking skills. It analyzes both the positive and negative effects of AI tools in education and how they influence students’ ability to analyze, evaluate, and create independent ideas. The paper also highlights the importance of balancing AI usage with traditional learning methods to ensure the development of strong cognitive and analytical skills in students.
Keywords: Artificial intelligence, critical thinking, education, students, learning process, cognitive skills, problem-solving, digital tools, independent thinking, innovation.